2022
DOI: 10.1111/tpj.15996
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis transcription factor TCP9 modulates root architectural plasticity, reactive oxygen species‐mediated processes, and tolerance to cyst nematode infections

Abstract: SUMMARY Infections by root‐feeding nematodes have profound effects on root system architecture and consequently shoot growth of host plants. Plants harbor intraspecific variation in their growth responses to belowground biotic stresses by nematodes, but the underlying mechanisms are not well understood. Here, we show that the transcription factor TEOSINTE BRANCHED/CYCLOIDEA/PROLIFERATING CELL FACTOR‐9 (TCP9) modulates root system architectural plasticity in Arabidopsis thaliana in response to infections by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…In soybean and eggplant, GmTCP19-Like (GmTCP19L) and SmTCP7a modulate resistance to Phytophthora sojae [ 22 ] and R. solanacearum [ 114 ], respectively, but the molecular mechanisms involved are still unknown. A recent report indicated that TCP9 modulates root system architectural plasticity in response to infections by the endoparasitic cyst nematode Heterodera schachtii via reactive oxygen species (ROS)-mediated processes in Arabidopsis, establishing a novel tolerance mechanism that mitigates the impact of biotic stress rather than targeting the causal agent [ 115 ].…”
Section: Biological Processes Modulated By Class I Tcpsmentioning
confidence: 99%
See 1 more Smart Citation
“…In soybean and eggplant, GmTCP19-Like (GmTCP19L) and SmTCP7a modulate resistance to Phytophthora sojae [ 22 ] and R. solanacearum [ 114 ], respectively, but the molecular mechanisms involved are still unknown. A recent report indicated that TCP9 modulates root system architectural plasticity in response to infections by the endoparasitic cyst nematode Heterodera schachtii via reactive oxygen species (ROS)-mediated processes in Arabidopsis, establishing a novel tolerance mechanism that mitigates the impact of biotic stress rather than targeting the causal agent [ 115 ].…”
Section: Biological Processes Modulated By Class I Tcpsmentioning
confidence: 99%
“…MpTCP1 senses ROS levels and affects the expression of several enzymes involved in ROS metabolism, mediating adaptive responses to heat stress [ 13 ]. In Arabidopsis , TCP9 modulates ROS homeostasis in response to nematode infection [ 115 ] and class I TCP double and triple mutants exhibit enhanced ROS production [ 78 ]. It was also reported that expression of moso bamboo PeTCP10 increases drought tolerance in transgenic Arabidopsis via ROS-regulated root growth [ 120 , 121 ].…”
Section: Modulation Of Class I Tcp Protein Activitymentioning
confidence: 99%
“…However, previous research showed that the decreased ROS production in the rboh D/F mutant resulted in smaller syncytia and females compared to wild-type plants (Siddique et al ., 2014; Chopra et al ., 2021). While too high or too low levels of ROS can be deleterious for plants, modulation of ROS homeostasis within non-deleterious levels can regulate many cellular and physiological processes (Mittler, 2017, Willig et al ., 2022). For instance, modulation of ROS homeostasis via WOX11 could possibly mediate changes in syncytial cell wall extensibility in response to the fluctuations in sucrose and turgor pressure due to nematode cyclic feeding behavior.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a quantitative trait loci allele of ATS40-3 that was identified with a Genome Wide Association Study affects the sex ratio of H. schachtii in Arabidopsis (Anwer et al ., 2018). Recently, we also showed that the transcription factor TCP9 modulates tolerance to H. schachtii via reactive oxygen species mediated processes (Willig et al ., 2022). However, it remains unknown if A. thaliana harbours significant genetic variation in tolerance to nematodes.…”
Section: Introductionmentioning
confidence: 99%